2019
DOI: 10.1111/eva.12880
|View full text |Cite
|
Sign up to set email alerts
|

Increased genetic marker density reveals high levels of admixture between red deer and introduced Japanese sika in Kintyre, Scotland

Abstract: Hybridization is a natural process at species range boundaries, but increasing numbers of species are hybridizing due to direct or indirect human activities. In such cases of anthropogenic hybridization, subsequent introgression can threaten the survival of native species. To date, many such systems have been studied with too few genetic markers to assess the level of threat resulting from advanced backcrossing. Here, we use 44,999 single nucleotide polymorphisms (SNPs) and the ADMIXTURE program to study two a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 54 publications
3
61
0
Order By: Relevance
“…in line with the gene-based theory of conservation (Petit, 2004). In our study area, we found approximately 43% of individuals are hybrids (McFarlane, Hunter, et al, 2020; and in the present study, we have identified 60 SNPs with both an excessive negative α and excessive negative β estimate, indicative of introgressive alleles moving from the introduced sika into the native red deer faster than expected.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…in line with the gene-based theory of conservation (Petit, 2004). In our study area, we found approximately 43% of individuals are hybrids (McFarlane, Hunter, et al, 2020; and in the present study, we have identified 60 SNPs with both an excessive negative α and excessive negative β estimate, indicative of introgressive alleles moving from the introduced sika into the native red deer faster than expected.…”
Section: Discussionsupporting
confidence: 88%
“…Hybrid deer tend towards an intermediate phenotype and thus are smaller, have smaller antlers, and are more likely to have the spots typical of sika than parental species red deer (Bartos et al, 1981). Initial hybridization may be constrained by the substantial size difference between species, but it is clear that at least some F1s and many backcrosses are fertile (Harrington, 1979;McFarlane, Hunter, et al, 2020;. While there is a trend from red deer in the north to sika in the south of Kintyre, the distribution of hybrids does not follow a cline, being instead concentrated in specific areas (Senn et al, 2010), and we have thus recently redefined this system as a "bivariate hybrid zone" (McFarlane, Hunter, et al, 2020;McFarlane & Pemberton, 2019;.…”
mentioning
confidence: 97%
“…Conversely, hybridization is also considered as “genetic pollution,” which will accelerate the extinction of native species ( Simon et al, 2020 ). Moreover, human activities are impacting the genetic makeup of an increasing number of native species ( McFarlane et al, 2020 ). On the other hand, frequent gene exchange makes elucidating the lineage relationships between species complicated, and thus, it is difficult to identify their lineages and evolutionary history accurately through a few genes or the mitochondrial genome.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Eryn McFarlane highlighted her work on anthropogenic hybridization between red deer ( Cervus elaphus ) and introduced sika deer ( Cervus nippon ). She found that a large proportion of the population were hybrid individuals and that locus‐specific introgression of alleles from sika into red deer could lead to the loss of endemic genetic variation 21 …”
Section: Speaker Institution Title Linkmentioning
confidence: 99%